Internalization of Pragmatic Education in Rahmatan Lil 'Alamin Islamic Religious Culture for Students in Educational Institutions - Ridwan Efend Ridwan Efend (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2022)
ABSTRACT (ENGLISH) This study aims to describe the internalization of pragmatic education in the Islamic religious culture of Rahmatan Lil'alamiin students at the State Junior High School 1 Sumbermalang. The research method uses qualitative. Determination of informants using purposive sampling. The data collection uses interview, observation, and documentation techniques. The data analysis uses the Miles & Haberman technique, namely data collection, data reduction, data display and conclusion drawing. The validity of the data uses source triangulation. The results of this study indicate the following: 1) habituation of prayer, such as the obligatory Duha prayer and Duhur prayer at school. PAI teachers emphasize how important prayer is for human spiritual needs, so teachers require congregational prayers at school so that students are also accustomed to praying together at home; 2) get used to harmonious relationships between children and other people. the teacher accustoms students to have empathy for others because humans are creatures who need each other; and 3) getting used to good relations between students and nature. Schools usually hold a